Biology Module for Immune System Material with Islamic Values as Learning Media - Maghfiroh, Istaqim Lailal; Sulistiyawati (Proceeding International Conference on Science and Engineering, 2020)
This research aims to develop a biology module for immune system material containing Islamic values as learning media. The physical form of the product in this development is printed media in the form of a module (printed materials). The Islamic content in the module is classified into the technical level as an effort for students’ self development. The product was validated and rated by a material expert, a media expert, and four peer reviewers. In this research development, a limited test was conducted to Biology teachers and 14 students of class XII of SMA Sains Wahid Hasyim. The instrument used in this development was a checklist questionnaire of qualitative data from the assessment results which was converted to quantitative data using a Likert scale. The results of the assessments from the material expert, media expert, and peer reviewers show that the percentage of ideality from the material expert is 88.7% in the Very Good category, from the media expert is 76% in the Good Category, from peer reviewers is 89.33% in the Very Good category, and the Biology teachers considered it Good with a percentage of ideality 79.9%. Meanwhile, the students’ responses showed that they strongly agree with the percentage of ideality 89%. Thus, the Biology Module for Immune System with Islamic values is appropriate to be used as learning media.